Economic impact of arecanut based cropping systems: A study of Dakshina Kannada district-Karnataka - Jayasekhar, S.; Jose, C.T.; Thamban, C.; Muralidharan, K. (Journal of Plantation Crops, 2012)
The present study was to quantify the economic impact of arecanut based cropping systems in south Karnataka region. It was observed that, farmers are predominantly following three different cropping systems such as 1) arecanut+banana 2) arecanut+cocoa and 3) arecanut+banana+pepper other than arecanut alone as monocrop. These systems were compared with the arecanut monocrop and found that the percentage increase in net returns from systems 1, 2 and 3 over monocrop were 32, 40 and 44 respectively. It was observed that, the percentage adoption of arecanut monocrop was 26, while it was 36, 11 and 27 for system 1, 2 and 3 respectively. The economic impact of different cropping systems were estimated by calculating the average cost per hectare, average yield and the net returns of each cropping system. The economic impact of each system has been worked out by combining the difference in net returns of each system from the arecanut monocrop, and percentage of adoption of each cropping system. The total economic impact in monetary terms due to adoption of cropping systems in the region was found to be Rs.819 million. The methodology used in this study for quantifying the economic impact of arecanut based cropping systems could be used in other cropping systems as well. Moreover, the quantified economic impact figures could be used as an input for formulating policy decisions related to arecanut.